DNA Replication Stress Phosphoproteome Profiles Reveal Novel Functional Phosphorylation Sites on Xrs2 in Saccharomyces cerevisiae. Issue 1 (1st May 2016) - Huang, Dongqing; Piening, Brian D; Kennedy, Jacob J; Lin, Chenwei; Jones-Weinert, Corey W; Yan, Ping; Paulovich, Amanda G
Abstract: In response to replication stress, a phospho-signaling cascade is activated and required for coordination of DNA repair and replication of damaged templates (intra-S-phase checkpoint) . How phospho-signaling coordinates the DNA replication stress response is largely unknown. We employed state-of-the-art liquid chromatography tandem-mass spectrometry (LC-MS/MS) approaches to generate high-coverage and quantitative proteomic and phospho-proteomic profiles during replication stress in yeast, induced by continuous exposure to the DNA alkylating agent methyl methanesulfonate (MMS) . We identified 32, 057 unique peptides representing the products of 4296 genes and 22, 061 unique phosphopeptides representing the products of 3183 genes. A total of 542 phosphopeptides (mapping to 339 genes) demonstrated an abundance change of greater than or equal to twofold in response to MMS. The screen enabled detection of nearly all of the proteins known to be involved in the DNA damage response, as well as many novel MMS-induced phosphorylations. We assessed the functional importance of a subset of key phosphosites by engineering a panel of phosphosite mutants in which an amino acid substitution prevents phosphorylation. In total, we successfully mutated 15 MMS-responsive phosphorylation sites in seven representative genes including APN1 (base excision repair); CTF4 and TOF1 (checkpoint and sister-chromatid cohesion); MPH1 (resolution of homologous recombination intermediates); RAD50 and XRS2 (MRX complex); and RAD18 (PRR). All of these phosphorylation site mutants exhibited MMS sensitivity, indicating an important role in protecting cells from DNA damage. In particular, we identified MMS-induced phosphorylation sites on Xrs2 that are required for MMS resistance in the absence of the MRX activator, Sae2, and that affect telomere maintenance.